Next-generation sequencing reveals additional HLA class I and class II alleles associated with type 1 diabetes and age at onset - Robino, Antonietta; Bevilacqua, Elena; Aldegheri, Luana; Conti, Andrea; Bazzo, Valentina; Tornese, Gianluca; Catamo, Eulalia (Frontiers in Immunology, 2024)
Introduction: Type 1 diabetes is an autoimmune disease with an significant genetic component, played mainly by the HLA class II genes. Although evidence on the role of HLA class I genes in developing type 1 diabetes and its onset have emerged, current HLA screening is limited to determining DR3 and DR4 haplotypes.This study aimed to investigate the role of HLA genes on type 1 diabetes risk and age of onset by extensive typing.Methods: This study included 115 children and young adults with type 1 diabetes for whom typing of HLA-A, -B, -C, -DRB1, -DRB3/4/5, -DQA1, -DQB1, -DPA1 and -DPB1 genes was conducted using Next Generation Sequencing.Results: We observed that 13% of type 1 diabetes subjects had non-classical HLA haplotypes that predispose to diabetes. We also found that compared to type 1 diabetes subjects with classical HLA haplotypes, non-classical HLA subjects had a significantly higher frequency of HLA-B*39:06:02 (p-value=0.01) and HLA-C*07:02:01 (p-value=0.03) alleles, known to be involved in activating the immune response. Non-classical HLA subjects also presented peculiar clinical features compared to classical HLA subjects, such as multiple diabetic antibodies and the absence of other autoimmune diseases (i.e., coeliac disease and thyroiditis).We also observed that subjects with early onset had a higher frequency of DQ2/DQ8 genotype than late-onset individuals. Moreover, subjects with late-onset had a higher frequency of alleles HLA-B*27 (p-value=0.003), HLA-C*01:02:01 (p-value=0.027) and C*02:02:02 (p-value=0.01), known to be associated with increased protection against viral infections.Discussion: This study reveals a broader involvement of the HLA locus in the development and onset of type 1 diabetes, providing insights into new possible disease prevention and management strategies.